PERSPECTIVES OF INDONESIAN UNDERGRADUATE STUDENTS ON READING PROFICIENCY AND COMMUNICATIVE COMPETENCE - Sinom, Patrick Adtya Pratama; Ena, Ouda Teda (Premise: Journal of English Education and Applied Linguistics, 2023)
The transformation of the world has brought communication into a complex system. This research focused on understanding communication from reading proficiency and communicative competence perspectives. It is aimed to find a correlation between reading proficiency and communicative competence in English as L2. The quantitative method with the correlational study was employed to analyze the data collected. The study was conducted at a private university in Yogyakarta. Thirty students participated in this research. The study employed a survey design using a questionnaire to collect the data. The result indicated a strong connection between reading proficiency and communicative competence. It implies that reading proficiency and communicative competence are connected.